Time use among rural households in Ethiopia: Implications for household welfare and productivity - Tigabu Degu Getahun; Jemberu Lulie Mekonnen (University of Bonn, Center for Development Research (ZEF), 2024)
This study investigates the dynamics of time allocation within Ethiopian rural households. Analysis of daily time allocation shows a contrast in total work hours between men and women, with women shouldering a significantly higher burden. This disparity suggests an incidence of time poverty among women. Further exploration presents the gendered division of labor within households with unpaid work entirely delegated to women and children and men undertaking only paid work. Women's simultaneous engagement in paid and unpaid work reduces their leisure time considerably, especially in low-income households. Moreover, the study analyses women's time use patterns and children's nutritional outcomes. We also analyze infrastructural and service access on time allocation; we find that improved access, particularly to electricity and agricultural technologies, reduces women's unpaid work and increases the leisure of all members of the household.
Keywords: J22; J16; B54; 330; Time-Use; Unpaid Work; Gender Inequality; Children's Diets; Technology